2005
DOI: 10.1248/bpb.28.2173
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Effect of 2',4',7-Trihydroxyisoflavone on the Expression of Matrix Metalloproteinase-1, 2 in Ultraviolet-B Irradiated Primary Cultured Old Aged Human Skin Fibroblasts

Abstract: Long term and repeated exposure of UV light on the skin often induces chronic skin diseases such as skin cancer as well as photoaging, and the mechanisms of these skin damages are closely associated with up-regulation of matrix metalloproteinase's (MMPs) activities. We investigated the effect of 2,4,7-trihydroxyisoflavone purified from the whole plants of Viola hondoensis W. BECKER et H BOISSIEU (Violaceae) on the expression of MMPs in UV-B irradiated old aged human skin fibroblasts. 2,4,7-trihydroxyisoflavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…These results correlated well with a previous report that UV irradiation of cultured human skin fibroblasts induced upregulation of MMP-1, but had no effect on MMP-2. 31) In conclusion, the present study has shown that spinasterol-Glc isolated from Stewartia koreana promotes production of collagen in UV-irradiated fibroblast cells via stimulation of procollagen synthesis and via inhibition of MMP-1 expression. The underlying mechanisms by which spinasterol-Glc stimulates production of collagen and also inhibits MMP-1 expression in UV-irradiated fibroblast cells need to be elucidated.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These results correlated well with a previous report that UV irradiation of cultured human skin fibroblasts induced upregulation of MMP-1, but had no effect on MMP-2. 31) In conclusion, the present study has shown that spinasterol-Glc isolated from Stewartia koreana promotes production of collagen in UV-irradiated fibroblast cells via stimulation of procollagen synthesis and via inhibition of MMP-1 expression. The underlying mechanisms by which spinasterol-Glc stimulates production of collagen and also inhibits MMP-1 expression in UV-irradiated fibroblast cells need to be elucidated.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that many plant extracts stimulate collagen production and inhibit matrix metalloproteinases during photoaging. 13,16) Most plant-derived compounds promote collagen production in human skin fibroblasts via inhibition of MMP expression 31) but only a few plant-derived compounds, such as obovatol, have been reported to stimulate collagen synthesis. 21) Our results suggest that spinasterol-Glc may stimulate expression of proa1 (I) and/or proa2 (I) genes in fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…2a). This result indicates that the inhibitory effect of 10‐HDA on MMP‐1 and MMP‐3 expression is not related to non‐specific cytotoxicity, as previously reported 32 …”
Section: Discussionsupporting
confidence: 83%
“…1B,C, 2C) is quite different from PTEN‐mediated regulation of MMP‐2 in glioma cells. However, no induction of MMP‐2 in fibroblasts upon UV irradiation has been reported by other groups (Fisher et al, 1996; Kawaguchi et al, 1996; Kut et al, 1997; Moon et al, 2005), implying that the regulation of MMP‐2 may not be mediated by PTEN in fibroblasts. This conclusion is also supported by our results showing that the transfection of PTEN genes did not affect MMP‐2 secretion (data not shown).…”
Section: Discussionmentioning
confidence: 89%